Dari Otoritas Teks ke Identitas Sosial: Pembacaan Hadis Masjid Pogung Dalangan Yogyakarta sebagai Konstruksi Identitas Keagamaan - Muhammad Fikri Lubis; Muhammad Taufiqqulhidayah Nur Waarits; Fikri Qurrata Ayunin; Mira Faizah (Journal of Hadith Studies, 2025)
This article examines the identity of ḥadīth interpretation at Masjid Pogung Dalangan (MPD), a mosque known for its active engagement in both conventional and digital daʿwah and its affiliation with the Salafi–Wahhabi movement. An academic problem arises from the tendency for ḥadīths used in daʿwah activities to be presented in a partial and predominantly textual manner. This study aims to analyze how practices of ḥadīth presentation at MPD shape patterns of understanding and the congregation's religious identity. The research employs a library-based approach complemented by field observation and a review of relevant literature. The findings indicate that the materiality of ḥadīth readings—displayed through LCD screens, posters, and social media—plays an active role in shaping the congregation’s theological and practical understanding. The limited presentation of ḥadīths to matn excerpts and translations without sharḥ encourages a textual and literal mode of reading, aligning with Salafi daʿwah strategies that emphasize textual clarity, simplicity of message, and effective transmission of religious teachings.